THE EFFECT OF PEER FEEDBACK TECHNIQUE IN TEACHING WRITING ON STUDENTS’ WRITING ACHIEVEMENT OF WRITING II COURSE AT ENGLISH DEPARTMENT FKIP LAMBUNG MANGKURAT UNIVERSITY - Furqoni, Nadya Isnan (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2019)
Providing student with clear feedback is one of the ways that can facilitate students to be able to write well. This study is aimed to find out the difference between students who are taught by using peer feedback and those who are taught by using teacher feedback.  This was an experimental research that used quantitative approach. The subjects of this research were students of Writing II of English Department of FKIP Lambung Mangkurat University. Writing II class A1 was the experiment group and Writing II class A2 was the control group. The data of this research were students’ writing achievement in both experiment and control class. The data analyzed by using SPSS (One-Way ANOVA). Ha was found 0.003 which meant that Ha was accepted. It showed that there was difference in students’ writing achievement between students in experiment and control class. It was proved that students who were taught by using peer feedback had higher achievement in writing than students who were taught by using teacher feedback. On the whole, it is suggested for students to improve their ability in proof reading and for the teachers, it is suggested to apply not only teacher feedback technique, but also peer feedback technique to their students in writing class.